Malignant granulosa cell tumor of testis with metastasis to liver: Case report and review of literature - Sandhya Bordiya; Kumari Priyanka; Dharmendra Garg (Indian Journal of Pathology and Microbiology, 2020)
We report a case of testicular granulosa cell tumor of adult type in a 65-year-old male patient who has presented with hepatic metastasis. Although, this type of sex cord stromal tumor is relatively common in the ovaries, it is extremely unusual in the testis, and it probably represents the rarest type of testicular sex cord stromal tumor.